Isolation of a Chinook Salmon Bafinivirus (CSBV) in Imported Goldfish Carassius auratus L. in the United Kingdom and Evaluation of Its Virulence in Resident Fish Species - Irene Cano; David Stone; Jacqueline Savage; Gareth Wood; Brian Mulhearn; Joshua Gray; Nick Stinton; Stuart Ross; Michaela Bonar; Nick G. H. Taylor; Kelly S. Bateman; Stephen W. Feist (Viruses, 2020)
This is the first record of a fish nidovirus isolated from a consignment of goldfish at the United Kingdom (UK) border. The full-length viral genome was 25,985 nt, sharing a 97.9% nucleotide identity with the Chinook salmon bafinivirus (CSBV) NIDO with two deletions of 537 and 480 nt on the ORF Ia protein. To assess the potential impact on UK fish species, Atlantic salmon, common carp and goldfish were exposed to the virus via an intraperitoneal (IP) injection and bath challenge. Moribundity was recorded in only 8% of IP-injected goldfish. A high viral load, ≈107 of the CSBV PpIa gene, was measured in the kidney of moribund goldfish. Mild histopathological changes were observed in the kidneys of challenged carps. Ultrastructural observations in renal tubule epithelial cells of goldfish showed cylindrical tubes (≈15 nm in diameter) and tubular structures budding spherical virions (≈200 nm in diameter) with external spike-like structures. Negative staining showed both circular and bacilliform virions. Seroconversion was measured in common carp and goldfish but not in Atlantic salmon. This study reinforces the potential risk of novel and emerging pathogens being introduced to recipient countries via the international ornamental fish trade and the importance of regular full health screens at the border inspection posts to reduce this risk.